P2P (BILATERAL) COMMUNICATION BETWEEN NodeMcu ESP8266 BOARDS USING ARDUINO IDE - TODICA, M. (Studia Universitatis Babeș-Bolyai Physica, 2020)
Bilateral communication between the boards NodeMcu ESP826 is achieved using the WI FI capabilities of these devices and particularly code based on Arduino IDE. The system is used to control servos, DC motors or led. The duplex communication allows feedback action between sender and receiver. Real time feedback is obtained by particularly connection of the servo to the board.